Diseño y construcción de un tanque para almacenar 2000 toneladas de aceite de palma basado en la norma api 650-2007 - Jiménez Pazmiño, Galo Enrique (2009)
At the present time, the palm oil in the Ecuador is important in the development of the nutritious industry; it tames and gives combustible alternative. This oil is used in the production this some products like margarines, soaps, oil gives table among others. The storage gives this oil it is in tanks steels with big volumes in sure places. In Emeralds one needs to build a tank for storage palm oil with a capacity of 2000 tons. This project was assigned the manufacturer Hidalgo & Hidalgo, which assigned me the dimensionamiento, gives the elements the tank (Fund, Corps, and Structures). it is for this reason that I carry out the design this the tank 2000 tons based on the norm API-650-2007 and to show the processes gives construction, inspection and testing give the same one it is needed to know the location this the assembly the tank to be able to examine some factors like the seismic area, the wind and superficial protection gives the tank. The result gives this design it is to establish a methodology construction elements and pieces, determined in calculations based on the norm API-650, including relative cost gives hardware, materials and concerning manpower to the project to facilitate the realization of budget in this work.